Peptides as therapeutics and active gene delivery vehicles for cancer treatment - Uppalapati, Lakshmi (Kansas State University, 2015)
Over the years proteins/peptides have evolved as promising therapeutic agents in the treatment of cancer. Considering the advantages of peptides such as their small size, ease of synthesis, tumor-penetrating ability and bio-compatibility, present report discusses proof of concept for 1. C1B5 peptide of protein kinase Cγ and a low dose of gemcitabine combination treatment for peritoneally disseminated pancreatic cancer and 2. dTAT peptide nanoparticles mediated gene (angiotensin II type 2 receptor gene) therapy for lung cancer. 1. A significant reduction in intraperitoneally (IP) transplanted pancreatic carcinoma growth was demonstrated with C1B5 peptide and gemcitabine co-treatment in an immunocompetent mouse model. Increased number of Granzyme B positive cells was observed in treated mice ascites, suggesting the involvement of immune response in tumor attenuation. The strong effect observed in combination treatment might be because of increase in lymphocyte recruitment by gemcitabine followed by C1B5 peptide mediated CD8+ T-cells or NK cells activation apart from direct cancer cell apoptosis. 2. To test dTAT peptide nanoparticles (dTAT NPs) mediated therapeutic gene delivery, luciferase reporter gene containing dTAT nanoparticles were synthesized (dTAT/pLUC/Ca2+). Synthesis conditions for nanoparticles were optimized based on dTAT/pLUC/Ca2+ nanoparticles transfection efficiency. With the optimized conditions, dTAT NPs containing AT2R, TRAIL or miR-34a pDNA (dTAT/pAT2R, dTAT/TRAIL or dTAT/miR- 34a) were synthesized. Therapeutic potential of these NPs was analyzed in lung adenocarcinoma containing mice by administering them intravenously (IV) or/and intratracheally (IV). Combination treatment with the IV injection of the new dTAT/pAT2R/Ca2+ formulation and the IT injection of the original dTAT/pAT2R/Ca2+ formulation is effective in attenuation of developed human bronchioloalveolar carcinoma in the SCID mouse lungs. Findings from the above mentioned studies have vital clinical relevance as it implies that peptides alone or when used as gene delivery systems may prove to be beneficial in the treatment of various stages of cancer.
Keywords: Cancer therapeutics; Nanoparticle; Intratracheal; Lung cancer